Central Treatment of Ketone Body in Rainbow Trout Alters Liver Metabolism Without Apparently Altering the Regulation of Food Intake - Comesaña, Sara; Velasco, Cristina; Conde-Sieira, Marta; Otero-Rodiño, Cristina; Míguez, Jesús M.; Soengas, José L. (Frontiers in Physiology, 2019)
We hypothesize that the presence in fish brain of a ketone body (KB) like β-hydroxybutyrate (BHB) alters energy homeostasis through effects on food intake and peripheral energy metabolism. Using rainbow trout (Oncorhynchus mykiss) as a model, we intracerebroventricularly (ICV) administered 1 µl·100 g-1 body mass of saline solution alone (control) or containing 0.5 µmol of BHB. In a fist set of experiments, BHB did not affect food intake 6 and 24h after treatment. In a second set of experiments, we evaluated 6h after ICV BHB treatment changes in parameters putatively related to food intake control in brain areas (hypothalamus and hindbrain) involved in nutrient sensing and changes in energy metabolism in liver. The absence of changes in food intake might relate to the absence of major changes in the cascade of events from the detection of KB through ketone-sensing mechanisms, changes in transcription factors, and changes in the mRNA abundance of neuropeptides regulating food intake. This response is different than that of mammals. In contrast, central administration of BHB induced changes in liver energy metabolism suggesting a decreased use of glucose and probably an enhanced use of amino acid and lipid. These responses in liver are different to those of mammals under similar treatments but comparable to those occurring in fish under food deprivation conditions